2008
DOI: 10.1111/j.1532-5415.2007.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers and Physical Function in Older, Obese Adults with Knee Pain and Self‐Reported Osteoarthritis After Intensive Weight‐Loss Therapy

Abstract: These results indicate that an intensive weight-loss intervention in older obese adults with knee pain can help improve inflammatory biomarkers and that changes in these concentrations showed associations with physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 46 publications
2
77
2
4
Order By: Relevance
“…However, it is not uncommon to observe elevated concentrations, especially in those with mid-stage to severe osteoarthritis. High circulating levels of TNF-a and IL-6 tend to be associated with lower physical function and slower walking speed in the elderly with knee OA, 31,36 but in the present study, this was not the case. Because TNF-a plays such a pivot role in the conservation of OA and is associated with greater radiographic of knee occurrences, 35 1 week of treatment is unlikely a long enough duration to observe decreases, especially considering that many of the subjects were inactive prior to the 6MWT.…”
Section: Discussioncontrasting
confidence: 69%
“…However, it is not uncommon to observe elevated concentrations, especially in those with mid-stage to severe osteoarthritis. High circulating levels of TNF-a and IL-6 tend to be associated with lower physical function and slower walking speed in the elderly with knee OA, 31,36 but in the present study, this was not the case. Because TNF-a plays such a pivot role in the conservation of OA and is associated with greater radiographic of knee occurrences, 35 1 week of treatment is unlikely a long enough duration to observe decreases, especially considering that many of the subjects were inactive prior to the 6MWT.…”
Section: Discussioncontrasting
confidence: 69%
“…30 However, no significant association found between CRP positivity and degree of knee pain and drug intake by patients. This contrasted other studies (Miller et al., 31 Marta et al…”
Section: Methodscontrasting
confidence: 55%
“…In addition to the several functional and morphological changes of the articular tissues, studies have shown altered inflammatory factors such as cytokines, including interleukin (IL)-6, tumor necrosis factor alpha (TNF-α), IL-15, IL-17, and IL-1 [3,[5][6][7][8], chemokines [9,10], receptors [4,11], and proteases [12,13], mainly on the lesion focus, showing the multifactorial nature of the disease. Due to the technical difficulty and risk of obtaining the biological samples, studies have examined the behavior of these inflammatory factors in the blood [10,14,15].…”
Section: Introductionmentioning
confidence: 99%